Dissolution and solubility of rhomboclase and arsenic-substituted rhomboclase phases at pH 2–10 and 25–45 °C. (September 2021) - Zhu, Yinian; Kong, Qiqi; Wei, Wanying; Zhu, Zongqiang; Tang, Shen; Zhang, Lihao; Yang, Hongqu
Abstract: The synthetic rhomboclase (Rbc) and arsenic-substituted rhomboclase phases (As-Rbc) were colorless well-formed rhombic thin tabular crystals. For their dissolution at initial pH 2–10 and 25–45 °C, the constituents were preferentially dissolved in the order of H5 O2 + ≫ AsO4  > SO4  > Fe for ~1 h, H5 O2 + ≫ AsO4  > Fe > SO4 from ~1 h to 720 h and finally H5 O2 + ≫ AsO4  > SO4 = Fe, suggesting an initial nonstoichiometric dissolution of As-Rbc to form Fe-rich outlayers and a final stoichiometric dissolution. The PHREEQC simulation indicated that the dissolved iron, sulfate and arsenate were present mainly as FeSO4 + /Fe(SO4 )2 - /Fe 3+, HSO4 − /FeSO4 + and H3 AsO4 0 /H2 AsO4 −, respectively. The SEM observation showed that the tops and edges of the crystals were dissolved and that the crystal surfaces were then gradually smoothed/rounded until all the edges and corners disappeared. For the dissolution at pH 2 and 25 °C for 720–2880 h, the ion-activity products [log IAP], which equal the solubility products [log K sp ] at equilibrium, and the Gibbs free energies of formation [Δ G f ° ] were estimated to be −8.80 ± 0.01 and −2706.44 ± 1.90 kJ/mol for the Rbc [(H5 O2 )1.434 Fe0.855 (SO4 )2 ·2H2 O], respectively. For the As-Rbc [(H5 O2 ) y (Fe) z [(AsO4 ) x (SO4 ) 1-x ]2 ·2H2 O], the log IAP and Δ G f ° values varied from −10.03 ± 0.03 to −8.89 ± 0.01 and from −2680.51 ± 2.05 kJ/mol to −2548.71 ± 1.94 kJ/mol, respectively. There was a strong negative correlation between the log IAP and the AsO4 /(AsO4 +SO4 ) molar ratio of As-Rbc. The results of this study provide new interesting thermodynamic data for the most acidic sulfates Rbc and As-Rbc; these data can be applied in the geochemical modeling and prediction of acid mine drainage systems. Graphical abstract: Image 1 Highlights: The synthetic As-rhomboclases were well-formed rhombic tabular crystals. The tops and edges of the crystals were first dissolved in dissolution. The crystal surfaces were gradually smoothed until all edges/corners disappeared. The components dissolved preferentially in the order of H5 O2 + ≫AsO4 >SO4, Fe. The log IAP at equilibrium was −8.89~-10.03 for (H5 O2 ) y (Fe) z [(AsO4 ) x (SO4 ) 1-x ]2 ·2H2 O.